2021
DOI: 10.1002/app.51235
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable calix[4]arene‐based gels by induction of water

Abstract: This study focused on controlling the stretching property of gels. This resilience is dependent on the water content in the calix [4]arene-based gel solvent system, where the stretching property of gels could be controlled upon the addition of water. The storage (G 0 ) and loss (G 00 ) moduli of the calix[4] arene-based gels prepared in solvent systems with different water contents were investigated via rheological measurements. By the strain sweeps, the values of G 0 decreased, while tan-delta increased with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…To measure the weight ratio of HMDS coupling agent on the surface of nano‐SiO 2 particles, TGA was carried out and it was found that 3.9 wt% of HMDS was attached on the nano‐SiO 2 surfaces, as reported in our previous study 20 . To measure the weight ratio of DVTMDS coupling agent on the surface of nano‐ATH particles, TGA analysis was also carried out, as displayed in Figure 3.…”
Section: Resultsmentioning
confidence: 86%
“…To measure the weight ratio of HMDS coupling agent on the surface of nano‐SiO 2 particles, TGA was carried out and it was found that 3.9 wt% of HMDS was attached on the nano‐SiO 2 surfaces, as reported in our previous study 20 . To measure the weight ratio of DVTMDS coupling agent on the surface of nano‐ATH particles, TGA analysis was also carried out, as displayed in Figure 3.…”
Section: Resultsmentioning
confidence: 86%